STRATEGI LIGHTENING THE LEARNING CLIMATE UNTUK MENINGKATKAN AKTIVITAS BELAJAR DALAM PEMBELAJARAN FIQIH DI MAN 1 PALEMBANG - Ahmad Wahyu Hidayat (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2020)
This study will parse the Application of The Learning Climate Lightening Strategy to Increase Learning Activities in Jurisprudence at MAN 1 Palembang. The research problem can be seen when the learning process of students tends to be more silent, only accepting material delivered by the teacher without giving questions or responses and so on. This research uses quantitative methods. In this study the sample of the study was class X. IPA.1 (27 people) as the control class and class X. IPA. 2 (33 people) experimental class. Research data were collected using the method of observation, questionnaires and documentation, then analyzed using the inductive approach and using the t test technique (T test). The results of his research are to find out the learning activities of students in class X IPA.1 (control class) in Jurisprudence learning that do not use the learning strategy of Lightening The Learning Climate in MAN 1 Palembang, the researchers distributed questionnaires to students who became the sample in this study, 27 class respondents control with 32 item items is a matter that is made according to indicators of learning activities including visual, verbal, listening, writing, drawing, metric, mental and emotional activities. Based on the recapitulation of respondents' answers it is known that the mean (x ') of the control class is 81.34 and the standard deviation (sd) is 3.14 while the recapitulation of the answers of the experimental class respondents is known the mean (x') is 94.81 and the standard deviation (sd) is 4.22. Because